How smallholder farmers adapt to climate change: Stories from East Africa - Anastacia Muthoni - Muthoni A (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2010)
Anastacia Muthoni is a widowed farmer living in Makengi, Kenya. In the video she talks about the difficulties associated with the lack of rainfalls, the irrigation of her farm, and how the farmers in the village have adapted to the changes in climate through crop diversification such as including cassava in their fields.